Characterization and modeling of microbial growth in the development of a non-dairy probiotic drink made from tarwi plant extract (Lupinus mutabilis S.) - Colque Cruz, Edith Jessica (2023)
The present study, had the purpose of developing a fermented non-dairy probiotic drink based on tarwi, for this purpose the legume was unmarked, and then obtained Tarwi Vegetable Extract (EVQ) by blending it, then proceeded to make mixtures with sucrose (6 and 12%) and inoculum of Saccharomyces boulardii (2 and 4%) thus obtaining a total of 4 treatments (A1 - A4), the inoculation was performed at 37 ° C with constant agitation at 20 RPM for a period of 24 hours; where at three-hour intervals readings of the biomass increase were made with a microscope and a neubauer chamber expressed in (cfu / ml) at intervals of 3 hours, curves and kinetic parameters of microbial growth were constructed with the mathematical model of Gompertz, a monitoring of ° Brix, density, pH, and% of acidity was carried out, a linear regression analysis was applied; finally the adjustment of the mathematical modeling was carried out. The results of the microbial growth kinetics showed the stages of microbial growth in all treatments, however, A1 showed the best fit in the kinetic parameters (C = 0.652, B = 1.296, M = 0.408). On the other hand, negative slopes with respect to ° Brix, density, pH, and a positive slope in acidity were observed in the linear regression of the physicochemical properties. The behavior of the kinetics of microbial growth and the physicochemical changes presented good parameters and characteristics of a probiotic drink.